Influence of age and aerobic fitness on the multifractal characteristics of electrocardiographic RR time-series - Lewis, Michael J.; McNarry, Melitta A. (Frontiers in Physiology, 2013)
Multifractal properties of electrocardiographic inter-beat (RR) time-series offer insight into its long-term correlation structure, independently of RR variability. Here we quantify multifractal characteristics of RR data during 24-hour diurnal-nocturnal activity in healthy participants. We tested the hypotheses that (1) age, gender and aerobic fitness influence RR multifractal properties, and that (2) these are influenced by circadian variation. Seventy adults (39 males) aged 19-58 years and of various fitness levels were monitored using 24-hour ECG. Participants were dichotomised by median age and fitness for sub-group analysis. Gender and fitness were independent of age (p=0.1, p>0.5). Younger/older group ages were substantially different (p<0.0005) and were independent of gender and fitness. Multifractality was quantified using the probability spectrum of Hölder exponents (h), from which modal h (h*) and the full-width and half-widths at half-maximum measures (FWHM, HWHM+ and HWHM-) were derived. FWHM decreased (p=0.004) and h* increased (p=0.011) in older people, indicating diminished long-range RR correlations and weaker anti-persistent behavior. Anti-persistent correlation (h*) was strongest in the youngest/fittest individuals and weakest in the oldest/least fit individuals (p=0.015). Long-range correlation (HWHM+/FWHM) was strongest in the fittest males and weakest in the least fit females (p=0.007-0.033). Multifractal RR characteristics in our healthy participants showed strong age-dependence with diminished long-range anti-persistent correlation in older people. Circadian variation of these characteristics was influenced by fitness and gender: fitter males and females of all ages had the greatest degree of multifractality or long-range order. Multifractal characterisation appears to be a useful method for exploring the physiological basis of long-term correlation structure in RR time-series as well as the benefits thereon of physical fitness training.